FINANCING RISK MANAGEMENT IN SHARIA FINANCIAL INSTITUTIONS - Widad Ulfatul Mawaddah (IJED: International Journal of Economy Development Research, 2022)
Management is the process of planning, organizing, directing, and controlling activities to achieve organizational goals effectively and efficiently by using organizational resources. Therefore, risk management is needed to identify, measure, monitor and control risks in accordance with sharia banking business activities. These steps are taken in order to mitigate risk by considering compliance with Sharia Principles. Risk is the potential loss due to the occurrence of certain events. Risk in the banking context is a potential event, both expected and unexpected, which has a negative impact on bank income and capital. Financing is funding provided by a party to another party to support planned investments, either by themselves or by institutions. In other words, financing is funding issued to support planned investments. The term financing basically means I believe, I trust, I believe, I put my trust. Islamic banks are banks that carry out business activities based on sharia principles, or Islamic legal principles regulated in the fatwa of the Indonesian Ulema Council such as the principles of justice and balance ('adl wa tawazun), benefit (maslahah), universalism (alamiyah), and do not contain gharar. , maysir, usury, injustice and unlawful objects.